Coupling responsible consumption and sustainable production using consumers’ green purchase behaviour - M.S. Narassima; Thenarasu Mohanavelu; Olivia McDermott; G. Harssheny; S.V. Shruthi; T. Suraj (Cleaner and Responsible Consumption)
Sustainability is imperative today, where climate change and environmental degradation pose existential threats. The United Nations' Sustainable Development Goal (SDG) 12 identifies that a large share of the world population consumes too little to meet their basic needs. Also, two-thirds of consumers worldwide are ready to pay a premium for sustainable products and services and engage in responsible consumption. This trend is driven by several variables, including increasing awareness of the impacts of irresponsible consumption and the desire to support brands promoting sustainability. This research aims to bridge Responsible Consumption and Sustainable Production (RCSP) by studying consumers' willingness to pay a premium for sustainability. The research employs a mixed-methods approach involving the development of a hierarchical model using Interpretive Structural Modelling (ISM), followed by MICMAC to cluster the variables based on their levels of importance and Confirmatory Factor Analysis (CFA) for validation. Initial brainstorming from industrial and academic experts was used to map the relationship between the variables. Scaled responses of 103 respondents were used to perform statistical validation, CFA, and hypothesis testing. The model fit indices reveal a significant fit. The findings signify how marketing and brand communication are vital in influencing the purchasing behaviour of consumers towards sustainable products and services. It helps producers know their consumer preferences and realign their brand's positioning in sustainability to increase trust and loyalty.